2003
DOI: 10.1002/yea.982
|View full text |Cite
|
Sign up to set email alerts
|

Cu,Zn superoxide dismutase in Rhodotorula and Udeniomyces spp. isolated from sea water: cloning and sequencing the encoding region

Abstract: The gene encoding the copper-zinc superoxide dismutase enzyme (SODC or Cu,Zn-SOD) has been cloned from several species of higher eukaryotes, but superoxide dismutase genes from moulds and yeast have not been studied extensively. For U. puniceus, the cloned nucleotide sequence contains all necessary information to produce a functional protein, which correlates with activity detected in cell homogenates, both under normal conditions and by copper induction experiments. Finally, we clearly showed that the key fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 44 publications
(36 reference statements)
0
4
0
Order By: Relevance
“…However, Hernández-Saavedra (2003) reports the presence of an active Cu, Zn-SOD after copper induction in pigmented yeast Udeniomyces puniceus. It suggests that the absence of Cu, Zn-SOD in pigmented yeast is complemented by the presence of carotenoproteins that act as an extra mitochondrial antioxidant (Moore et al 1989).…”
Section: Discussionmentioning
confidence: 95%
“…However, Hernández-Saavedra (2003) reports the presence of an active Cu, Zn-SOD after copper induction in pigmented yeast Udeniomyces puniceus. It suggests that the absence of Cu, Zn-SOD in pigmented yeast is complemented by the presence of carotenoproteins that act as an extra mitochondrial antioxidant (Moore et al 1989).…”
Section: Discussionmentioning
confidence: 95%
“…The absence of Cu/Zn-SOD in a pigmented yeast has been accepted as a general rule. Some authors suggest that the absence of Cu/Zn-SOD in pigmented yeast is complemented by the presence of caroteno proteins that act as an extra mitochondrial antioxidant [41] …”
Section: Debaryomyces Hanseniimentioning
confidence: 99%
“…The absence of SODC is not a rule for pigmented yeast Fragments of 485-487 nucleotides were obtained, which contain information for theoretical products of 153-154 amino acids [41] stability at pH 6.0-7.0, surviving boiling for 10 min without losing more than 60% of activity. In sequencing analysis, a peptide obtained by trypsin digestion was found to have 85% identity to the S. cerevisiae Cu/Zn-SOD [38].…”
Section: Debaryomyces Hanseniimentioning
confidence: 99%
“…Recent genetic and biochemical experiments revealed that in Rhodotorula mucilaginosa and Rhodotorula graminis changes in the structure of the SOD1 gene generate stop codons at different positions, which correlates with the absence of peptides or active proteins in the cells. however, for other basidiomycetous yeasts, such as R. glutinis and U. puniceus, the cloned nucleotide sequence contains all necessary information to produce a functional protein (16,20). Moreover, studies with S. cerevisiae cells lacking the cytosolic Sod1, showed that cadmium was removed twice as effectively as in the control strain, while those deficient in the mitochondrial Sod2 exhibited poor metal absorption (1).…”
Section: Oxygen Metabolism Affects Growth On CDmentioning
confidence: 99%